2020
DOI: 10.2147/dmso.s255908
|View full text |Cite
|
Sign up to set email alerts
|

<p>Urine Glucose Excretion Attenuates the Association Between Lipid Accumulation Product and Serum Uric Acid in Subjects with Prediabetes</p>

Abstract: Purpose: Obesity is known to be strongly associated with hyperuricemia. Moreover, the impact of urine glucose excretion (UGE) on serum uric acid (UA) levels has gained much more attention in recent years. Yet concern is raised about whether UGE influences the relationship between obesity and hyperuricemia. The aim of this study was to assess the effect of UGE on the association between lipid accumulation product (LAP), a novel marker of visceral adipose accumulation, and UA in subjects with prediabetes. Materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…A prior study demonstrated that persons with hypertension showed favorable relationships between the TyG index and hyperuricemia [30]. But when the above indices are evaluated to predict the HUA, LAP index shows the highest predictive value, with an AUC of 0.71, was responsible for increased risk of hyperuricemia, which has similar result with the prior reports [31,32]. When LAP index exceeds 39.37, its sensitivity and speci city to predict HUA are 80.00 and 52.00% respectively.…”
Section: Discussionsupporting
confidence: 76%
“…A prior study demonstrated that persons with hypertension showed favorable relationships between the TyG index and hyperuricemia [30]. But when the above indices are evaluated to predict the HUA, LAP index shows the highest predictive value, with an AUC of 0.71, was responsible for increased risk of hyperuricemia, which has similar result with the prior reports [31,32]. When LAP index exceeds 39.37, its sensitivity and speci city to predict HUA are 80.00 and 52.00% respectively.…”
Section: Discussionsupporting
confidence: 76%
“…Central obesity can be evaluated using various indices, and LAP was the strongest predictor for the occurrence of hyperuricemia in both sexes in our results. A Chinese study of 3645 subjects showed that LAP was positively associated with UA in both sexes, and high LAP was significantly associated with an increased OR for hyperuricemia (2.07, 95% confidence interval: 1.66-2.58, p < 0.001) [45]. Various biochemical metabolic processes may explain why LAP is a causative factor for the development of hyperuricemia.…”
Section: Discussionmentioning
confidence: 99%